FUNGSI SURAU DALAM MASYARAKAT MINANGKABAU DI KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Putri, Hildayani; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research wascarried out in Kinali District, WestPasaman Regency, West Sumatra Province. Theaim of thisresearch is to find out how the Surau functions in the past and present. To find out changes in the function of the Surau inthe past and present. Inthis research, thetechnique of taking subjects using snowball sampling was used inthis research. The theoryused in this research uses Social Change Theory and Functional Structural Theory. Thisresearch uses a qualitativeapproach with a descriptivetype. To obtain relevantresearch results, the research conducted interviews with 7 subjects and made direct observations inthe field. The results of thisresearch are thatthe surau in the past and present has experienced many changes both in terms of the building and the function of the surau itself. With the changes in the function of the Surau that are currently visible, there have been many changes in the behavior of the people who adhere to the traditional understanding coded as syarak syarak basandi kitabbullah which has made people increasingly abandon the function of the Furau and even now the function of the Surau can be said to be invisible or fading. With this phenomenon or reality, it is hoped that policy from the government and awareness from the community itself can restore the function of the Surau which has faded or been lost. Keywords: Changes, Functions of Surau, Minangkabau Society